Tetracycline and Acne Vulgaris: A Clinical and Laboratory Investigation. Issue 5888 (10th November 1973) - Cunliffe, W. J.; Forster, R. A.; Greenwood, N. D.; Hetherington, C.; Holland, K. T.; Holmes, R. L.; Khan, S.; Roberts, C. D.; Williams, M.; Williamson, B.
Abstract : A satisfactory clinical response to long-term oral tetracycline treatment was associated with a mean serum tetracycline of 1·98 μg/ml. The surface lipid showed an increased triglyceride, decreased free fatty acids, and decreased cholesterol, and the amount of keratin within the pilosebaceous duct was reduced. At this dose level there was no quantitative decrease in the bacterial flora though there was a decrease in the fatty acids. We believe that the latter was due to a direct inhibition by tetracycline on extracellular lipases.